Threats of Data Leakage in Military Security Systems In the Regional Military Command III/Siliwangi - Indriyana, Diana; Prasetyono, Budi; Mado, Aloysus (Pusat Studi Politik dan Kebijakan Strategis Indonesia (POLKASI), 2025)
This research investigates the threat of data leakage to the military security system in the Kodam III/Siliwangi region. While advancements in information technology have positively impacted society, they also bring the threat of cybercrime. The Indonesian government has responded by enacting the Personal Data Protection Law and strengthening inter-agency collaboration to prevent and address cybercrimes. The threat of data leakage in the Kodam III/Siliwangi region falls under non-physical and unconventional military threats, posing risks to national security and social stability.